2013
DOI: 10.2136/vzj2013.01.0005
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Patterns of Carbon Dioxide Flux in Crop and Grass Land‐Use Systems

Abstract: Understanding the field‐scale variability of CO2 fluxes in space and time under different land‐use conditions is important for designing efficient sampling schemes for monitoring C loss from soil. The objectives of this study were to characterize the variability structure of CO2 fluxes and its change throughout a year, evaluate the temporal stability of spatial CO2 flux patterns, and quantify relationships with biotic and abiotic factors in crop and grass systems. In an 80‐ by 60‐m field divided into grass and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 57 publications
2
13
0
Order By: Relevance
“…Growing season, cumulative soil-surface CO 2 effluxes ranged from 2.6 to 7.8 Mg CO 2 -C ha −1 with 4.6, 4.5, and 21 as the mean, median, and percent coefficient of variation, respectively. These data are consistent with those commonly reported in the literature (Guzman and Al-Kaisi, 2014;Kreba et al, 2013;Kaspar and Parkin, 2011;Vargas et al, 2010;Pumpanen et al, 2003). Significant intra-crop management zone main effect or the interaction by date were observed for weekly sampled soilsurface CO 2 efflux in the CC and CCW but not for C-s and c-S cropping systems when analyzed across all years (Table 1 and 2).…”
Section: Soil-surface Carbon Dioxide Effluxessupporting
confidence: 91%
See 2 more Smart Citations
“…Growing season, cumulative soil-surface CO 2 effluxes ranged from 2.6 to 7.8 Mg CO 2 -C ha −1 with 4.6, 4.5, and 21 as the mean, median, and percent coefficient of variation, respectively. These data are consistent with those commonly reported in the literature (Guzman and Al-Kaisi, 2014;Kreba et al, 2013;Kaspar and Parkin, 2011;Vargas et al, 2010;Pumpanen et al, 2003). Significant intra-crop management zone main effect or the interaction by date were observed for weekly sampled soilsurface CO 2 efflux in the CC and CCW but not for C-s and c-S cropping systems when analyzed across all years (Table 1 and 2).…”
Section: Soil-surface Carbon Dioxide Effluxessupporting
confidence: 91%
“…Although Wilson and Al-Kaisi (2008) reported that N applications decreased soil-surface CO 2 effluxes for corn rotations in Iowa, Guzman and Al-Kaisi (2014) reported that N application can result in greater potential C inputs to the soil. Kreba et al (2013) reported that soil-surface CO 2 effluxes in a mowed tall fescue and clover system was correlated farther across space and time than effluxes in a winter wheat (Triticum aestivum L.) cropping system. Kreba et al (2013) also reported that soil temperature controlled temporal variability of soil-surface CO 2 effluxes in both the annual and perennial systems but did not control the spatial variability.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…We carefully removed any litter and crop residuals at the sampling position and extracted the cores directly at the soil surface. The lateral distance between the sampling positions was 0.50 m with two nests of increased sampling intensity (distance: 0.25 m) in the middle of each treatment as demonstrated by Kreba et al (2013). The samples were taken prior to seeding in the end of March 2014.…”
Section: Experimental Site and Sampling Strategymentioning
confidence: 99%
“…It is well known that carbon transformation and respiration are strongly influenced by nutrient availability, soil type, soil water content, and soil temperature (Heimann and Reichstein, 2008;Kreba et al, 2013;Raich and Tufekcioglu, 2000). Scott-Denton et al (2003) studied seasonal changes in soil respiration rates and their variances to identify possible covariates (soil temperature, soil water content, soil C) for upscaling respiration measurements.…”
Section: Introductionmentioning
confidence: 99%